The remedy of furlough removing arbitrariness in a controversial procedural recourse (Philippine Law Journal, 2021)
Nowhere is the disparity between the social elite and the poor of Philippine society more apparent and more perverted than in the practical application of the law. The long history of revering or giving special treatment to those who have wealth and high political status has made varied manifestations in the legal process. This circumstance is readily apparent in some detainees' ostensible enjoyment of "prison furloughs," a remedy absent in the current rules of criminal procedure. Readily a subject of news headlines and popular controversies, prison furloughs have become indications of the legal process' arbitrariness, unfairness, and partiality. Despite the outrage that follows announcements of furloughs for powerful individuals, there exists no critique, more so an analysis, of the remedy of furlough- its source, bases, effects, and implications in contemporary legal literature. This Article is the first to dissect this legal concept. The authors argue that the highly discretionary and arbitrary nature of furloughs opens it to an equal protection challenge because it permits discrimination. An analysis of the cases where furlough has been denied and granted will show that persons similarly situated were clearly not treated alike. Despite this, the authors are of the opinion that "furloughs," in theory, may be an additional remedy for the accused. This is anchored on the rights of the accused and the purpose of preventive imprisonment. Thus, the remedy is not for the abolition of "furloughs," but for the Supreme Court to provide miles and guidelines for its application. Finally, taking from a review of domestic and international jurisprudence, this Article sets out standards on when furlough may be considered fair and reasonable in order for it to become available to all defendants, regardless of power, wealth, popularity, social standing, or counsel.